The Journey of a Communication Skills Educator: Motivating Factors for Commitment and Sustainability - England, Kelli; Bogetz, Jori; Lau, Nancy; Wood, Gordon J.; Trowbridge, Amy (Journal of pain and symptom management, 2025)
Communication is critical to improving patient and family outcomes, yet clinicians remain undertrained. Effective communication training takes significant investments in personnel and programming. Little is known about what motivates and sustains clinician educators in such programs. This qualitative study aimed to learn more about (1) what motivates clinician communication skills educators (CSEs) to improve their own communication and educate others and (2) what sustains them in this work. PedsTalk is a communication training program based on the VitalTalk model of small group role play within a single institution’s Department of Pediatrics. We conducted a thematic analysis of one-on-one interviews of PedsTalk faculty CSEs focused on the experiences that motivated them to improve their own communication and commitment to teaching and sustaining these skills. 17 CSEs participated, representing 8 specialties. The majority had 7 or more years of experience in their field (post-training). Thematic content analysis revealed 3 major themes: Drive: My choices reflect what matters to me; Growth: My efforts have impact; and Connection: What sustains me. The relationship between communication and health equity was highlighted across themes. These themes that emerged mapped onto the primary sources of intrinsic motivation according to self-determination theory: autonomy, competence, and relatedness, respectively. CSEs are intrinsically motivated by the drive to work on what matters to them, opportunities for growth as a communicator and educator, and their connection to others in this work. Educators and leaders can utilize these factors to build and sustain momentum in their programs.